Phenol Red Adsorption from Aqueous Solution on the Modified Bentonite - Nguyen Le My Linh; Tran Duong; Hoang Van Duc; Nguyen Thi Anh Thu; Pham Khac Lieu; Nguyen Van Hung; Le Thi Hoa; Dinh Quang Khieu (Journal of Chemistry)
In the present work, the modified bentonites were prepared by the modiﬁcation of bentonite with cetyltrimethylammonium bromide (CTAB), both cetyltrimethylammonium bromide and hydroxy-Fe cations and both cetyltrimethylammonium bromide and hydroxy-Al cations. X-ray diffraction (XRD), thermal analysis (TG-DTA), infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and nitrogen adsorption/desorption isotherms were utilized to characterize the resultant modified bentonites. The modified bentonites were employed for the removal of phenol red dye from aqueous solution. Phenol red adsorption agreed well with the pseudo-second-order kinetic model. The equilibrium data were analyzed on the basis of various adsorption isotherm models, namely, Langmuir, Freundlich, and Dubinin‒Radushkevich models. The highest monolayer adsorption capacity of phenol red at 30°C derived from the Langmuir equation was 166.7 mg·g−1, 125.0 mg·g−1, and 100.0 mg·g−1 for CTAB‒bentonite, Al‒CTAB‒bentonite, and Fe‒CTAB‒bentonite, respectively. Different thermodynamic parameters were calculated, and it was concluded that the adsorption was spontaneous (∆G° < 0) and endothermic (∆H° > 0), with increased entropy (∆S° > 0) in all the investigated temperature ranges.